2000
DOI: 10.1073/pnas.050400997
|View full text |Cite
|
Sign up to set email alerts
|

Mantle cell lymphoma is characterized by inactivation of the ATM gene

Abstract: In mantle cell lymphoma (MCL), the translocation t(11;14) is considered the cytogenetic hallmark of the disease. Recently, however, deletion of the chromosomal region 11q22-q23 has been identified as a frequent event in this type of cancer, indicating the existence of a pathogenically relevant tumor suppressor gene in this region. The deleted segment contains the ATM (ataxia telangiectasia mutated) gene. ATM is an interesting candidate as a tumor suppressor gene because constitutive inactivation of the gene pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
149
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 221 publications
(160 citation statements)
references
References 60 publications
7
149
2
Order By: Relevance
“…Suggested candidates for tumour suppressor genes and protooncogenes at the chromosomal regions which are frequently lost and gained, respectively, include the ATM gene at 11q23.1 (Bullrich et al, 1999;Schaffner et al, 2000), the TP53 gene at 17p13.1 (Stokke et al, 2000), and the BCL-2 gene at 18q21 (Monni et al, 1997). Other tumour suppressor genes and protooncogenes, which are located within the frequently altered regions, include p16INK4a (9p21), RB-1 (13q14), BCL6 (3q27), CCND3 (6p), and c-MYC (8q24).…”
Section: Discussionmentioning
confidence: 99%
“…Suggested candidates for tumour suppressor genes and protooncogenes at the chromosomal regions which are frequently lost and gained, respectively, include the ATM gene at 11q23.1 (Bullrich et al, 1999;Schaffner et al, 2000), the TP53 gene at 17p13.1 (Stokke et al, 2000), and the BCL-2 gene at 18q21 (Monni et al, 1997). Other tumour suppressor genes and protooncogenes, which are located within the frequently altered regions, include p16INK4a (9p21), RB-1 (13q14), BCL6 (3q27), CCND3 (6p), and c-MYC (8q24).…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Recent studies, including a number of oligonucleotide array studies, revealed additional biochemical abnormalities in mantle cell lymphoma, such as defects in the apoptotic pathway, cell cycle progression and DNA repair. [5][6][7][8][9][10] To further understand the biology of this type of B-cell neoplasm, one approach is to examine the somatic hypermutation of the variable region of the immunoglobulin heavy chain (V H ) gene. In chronic lymphocytic leukemia, it has been shown that a subset of cases has relatively high levels of V H somatic mutation, and mutated cases were associated with better clinical outcome when using o98% homology as the cutoff.…”
mentioning
confidence: 99%
“…This region harbors the DNA damagesensing ATM (ataxia telangiectasia mutated) gene and it has previously been shown that loss of one allele and mutation of the remaining allele is associated with progressive disease. 21 Located in the adjacent chromosomal region, 11 Mb telomeric to ATM, is the gene encoding histone H2AX. This protein is suggested to be a genomic caretaker requiring both alleles for full tumor-protective function.…”
Section: Discussionmentioning
confidence: 99%